A critical role for both CD40 and VLA5 in angiotensin II-mediated thrombosis and inflammation - (:unkn) unknown (WILEY, 2018)
Angiotensin II (Ang-II)-induced hypertension is associated with accelerated thrombus formation in arterioles and leukocyte recruitment in venules. The mechanisms that underlie the prothrombotic and proinflammatory responses to chronic Ang-II administration remain poorly understood. We evaluated the role of CD40/CD40 ligand (CD40L) signaling in Ang-Il-mediated microvascular responses and assessed whether and how soluble CD40L (sCD40L) contributes to this response. Intravital video microscopy was performed to analyze leukocyte recruitment and dihydrorhodamine-123 oxidation in postcapillary venules. Thrombus formation in cremaster muscle arterioles was induced by using the light/dye endothelial cell injury model. Wild-type (WT), CD40, and CD40L(-/-) mice received Ang-II for 14 d via osmotic minipumps. Some mice were treated with either recombinant sCD40L or the VLA5 (very late antigen 5; alpha 5 beta 1) antagonist, ATN-161. Our results demonstrate that CD40(-/-), CD40L(-/-), and WT mice that were treated with ATN-161 were protected against the thrombotic and inflammatory effects of Ang-II infusion. Infusion of sCD40L into CD40(-/-) or CD40L(-/-) mice restored the prothrombotic effect of Ang-II infusion. Mice that were treated with ATN-161 and infused with sCD40L were protected against accelerated thrombosis. Collectively, these novel findings suggest that the mechanisms that underlie Ang-Il-dependent thrombotic and inflammatory responses link to the signaling of CD40L via both CD40 and VLA5.
Keywords: sCD40L thrombosis; leukocytes; platelets; endothelium; hypertension; ALPHA-5-BETA-1 INTEGRIN; MICROVASCULAR RESPONSES; GLYCOPROTEIN IIB/IIIA; SOLUBLE CD40L; LIGAND; LEUKOCYTE; PLATELETS; TRIGGERS; BINDING; HYPERTENSION